1997
DOI: 10.1104/pp.114.1.185
|View full text |Cite
|
Sign up to set email alerts
|

CO2 and Water Vapor Exchange across Leaf Cuticle (Epidermis) at Various Water Potentials

Abstract: ~ ~Cuticular properties affect the gas exchange of leaves, but little is known about how much CO, and water vapor cross the cuticular barrier or whether low water potentials affect the process. Therefore, we measured the cuticular conductances for CO, and water vapor in grape (Vitis vinifera 1.) leaves having various water potentials. l h e lower leaf surface was sealed to force all gas exchange through the upper surface, which was stoma-free. In this condition both gases passed through the cuticle, and the CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
201
1
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(213 citation statements)
references
References 17 publications
5
201
1
6
Order By: Relevance
“…It approached half of E n observed upon ABA treatment, suggesting that water loss through the abaxial cuticle was close to that of the adaxial cuticle. Assuming that water loss through the cuticle was similar on both leaf sides (i.e., negligible part played by water vapor leaks through ABA-treated stomata), we inferred that total cuticular water loss from both sides accounted for 30% of E n , the remaining 70% being due to incomplete stomatal closure in the dark, in agreement with previous estimates in grapevine (27,35). Moreover, we found a significant effect of the genotype on cuticular water loss (P < 0.001).…”
Section: Cuticular Water Losses: Tight Genetic Control For a Small Frsupporting
confidence: 80%
“…It approached half of E n observed upon ABA treatment, suggesting that water loss through the abaxial cuticle was close to that of the adaxial cuticle. Assuming that water loss through the cuticle was similar on both leaf sides (i.e., negligible part played by water vapor leaks through ABA-treated stomata), we inferred that total cuticular water loss from both sides accounted for 30% of E n , the remaining 70% being due to incomplete stomatal closure in the dark, in agreement with previous estimates in grapevine (27,35). Moreover, we found a significant effect of the genotype on cuticular water loss (P < 0.001).…”
Section: Cuticular Water Losses: Tight Genetic Control For a Small Frsupporting
confidence: 80%
“…Thus, even if stomatal closure occurs with increasing salinity, the drop in CO 2 fixation due to metabolic causes will maintain a level of substomatal CO 2 that will not limit CO 2 fixation to a greater extent than in controls. Nevertheless, patchy stomatal closure [6] and changes in cuticular [5] and g m [7] must be considered. There is an increasing body of evidence indicating that g m decreases in response to drought and salinity [11,13,20].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in agreement with findings of Aracon et al (2004) who investigated the effect of vermicompost to reduce water deficit stress. Water deficit stress increased proline (Khalid, 2006;Aslani et al, 2009) and decreased total protein (Boyer et al, 1997;Good and Stonet, 1994) as many previous studied have reported. Non Structural Sugars Vermicompost, and vermicompost and water deficit stress interaction effects significantly on non-structural sugar (Table 3).…”
Section: Resultsmentioning
confidence: 78%
“…Water stress induces severe degradation in protein content of soybean leaves (Purcell and King, 1996). Water channel proteins such as acupurine and macromolecules such as proteins, have the role of protective factors, increased with drought stress (Boyer et al, 1997), while dehydration cause protein degradation and destruction of complex macromolecules and to stop construction typical set of proteins in the translation stage (Kafi and Damghani, 2003). Irigoyen et al, (1992) reported that protein degradation in mature leaves cause reduction in protein, and causing an increase in free amino acid concentrations including proline.…”
Section: Introductionmentioning
confidence: 99%